Optimasi Luas Petak Distribusi Irigasi Terputus-Putus Untuk Padi Sawah Pada Daerah Irigasi Air Tanah Dangkal - Muhammad Idrus; I Gde Darmaputra; Andy Eka Saputra (Jurnal Ilmiah Teknik Pertanian - TekTan, 2020)
The research was conducted in rainfed paddy  field at Cisarua Village, Natar  Sub District, Lampung Selatan Region to find out the area of plot distribution irrigation water to obtained the maximum area will be irrigated and the maximum net income. The treatment of intermittent irrigation are the intermittent irrigation with area plot distribution of water irrigation of 1,000 m2, 2,000 m2, 3,000 m2, 4,000 m2, and  5,000 m2. Preparation of seedling for the intermittent irrigation treatment using paddy field.   The treatment the intermittent irigation were using transplanting of 1 young seedling (18 days after seeding) at wider space 22 cm x 22 cm with range legowo 5:1. The results of these research showed that the total amount water application for plowing, harrowing, and leveling namely 656 m3/ha, but for growing paddy plant namely 626 m3/ha for each apply water irrigation.  Icreasing the area plot distribution of water irrigation so that the area paddy field will be irrigated also increase with the same of pumping discharge.  The maximum area paddy field can be irrigated with pumping capacity of ground water of 1,243 l/dt namely 1.1 ha with combination 2 plot distribution water irrigation with size 4.000 m2 each and 1 plot distribution water irrigation with size 3,000 m2 per planting season and obtained the maximum net income of Rp 19,414,333.   The average paddy prodcution obtained 7,366.7 kg/ha with amount water irrigation application 3.782 m3/ha. The Water irrigation productivity and the total water productivity of 1.95 and 0.91 kg/m3 repectively. Keywords: irigasi intermittent irrigation, amout water irrigation application, maximum area can be irrigated, maximum net income, production and water productivity.